Análise das condições de trabalho dos agentes comunitários de saúde de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2011)
The working conditions are related to the work environment and their risk factors, as well as the social, administrative and safety conditions. The purpose of the study was to analyse the working conditions of Community Health Agents (CHA) from Manaus- Amazonas. Quantitative, descriptive and analytical study, held in the public health of Manaus, in 4 urban sanitary districts. The sample consisted of 369 CHA. Data were collected by questionnaire. The information was structured in 3 variables: profile of CHA; occupational hazards, safety and health at work. The variables have converged to form the outcome variable, analyse of working conditions of the CHA. Project approved under the CAAE No 0258.0.115.000-10. The results show an average age of 40 years, prevalence of females, 321 women; complete high school among 307 CHA; Technical Community Health Agent (TCHA) course frequented by 289; In all there are 353 CHA who do not have the title of TCHA. Residents in the community totaling 271 CHA with an average time of 17.4 years. The CHA that participate in social activity in the community are 150. The main occupational hazards are: physical - sun exposure 352; high temperature 289; chemicals - dust 198; biological - tuberculosis 250. The innumerable ergonomic risks originating from long walks, 231; prolonged standing posture, 187; insufficient furniture, 326; lack of physical space in the health unit, 347; stressful professional activity 169; and, 255 also serve community requests out of the working hours. Among the risks of accidents, are inadequate physical arrangement 305, risk of assault 212; improper storage 201. The finding on the safety and health shows that 261 CHA ignore health of the worker; 251 had not received training / guidance on occupational risks in the profession of CHA; and 319 do not perform occupational exams; 282 did not receive personal protection equipment for work. About the health, there are overweight in both sexes. The most commonly reported health problems are musculoskeletal, 269, and the cardiovascular, 155 records. Other common injuries were verbal aggression, fall, sun burn, dog bite. The rate of absenteeism involved 215 CHA. It is concluded that the working conditions of the Community Health Agents of Manaus are inadequate for the lack professional valorization, high frequency of occupational hazards, lack of actions in safety and health at work. The assessment points to a serious mismatch regarding CHA, health care professionals that promote health, but at the same time, they do not have it
Keywords: Profissional da saúde; Saúde do trabalhador; Riscos ocupacionais; Condições de trabalho; Atenção básica à saúde; Health personnel; Health worker; Occupational risks; Working conditions; Primary health care; CIENCIAS DA SAUDE: SAUDE COLETIVA